When to warn – Update on interpretation of MEP. Issue 3 (March 2016) - MacDonald, D.B.
Abstract : There are two types of intraoperative motor evoked potentials (MEPs): single-pulse spinal epidural D-waves and pulse train muscle responses. Amplitude criteria apply to D-waves because they resist anesthesia and exhibit <10% trial-to-trial amplitude variability. For intramedullary spinal cord tumor (IMSCT) surgery, the transcranial electric stimulation D-wave warning criterion is >50% reduction because this correlates to long-term motor outcome. For peri-Rolandic brain surgery, the direct cortical stimulation D-wave warning criterion is >30% reduction. Muscle MEPs exhibit problematic variability and high sensitivity to anesthesia and central corticospinal pathway compromise. Disappearance is a major criterion because it correlates with postoperative weakness when irreversible. For IMSCT monitoring, marked (>80%) amplitude deterioration is an additional minor warning criterion. For other spinal cord monitoring, marked reduction can be an additional moderate warning criterion. For supratentorial, brainstem and facial nerve muscle MEP monitoring, >50% reduction is an additional major warning criterion. However, this depends on the degree of preceding trial-to-trial variability: when >50%, a larger decrement is needed; the reduction should be visually obvious and clearly exceed variability. Threshold elevation or morphology simplification criteria remain controversial.